Exploration of Biomechanical and Biooptical Sensors on Cardiac Monitor on Carotid Pulse - Putra, Wahyu Ramadhan; Yulianto, Endro; Faizal, Ajesh (Jurnal Teknokes, 2024)
Cardiovascular diseases are a significant global health concern, often requiring timely and accurate monitoring for effective management. Traditional heart monitoring devices face limitations, such as inadequate real-time data and suboptimal accuracy. This study aims to enhance the detection of carotid pulse signals by comparing the performance of two sensor types: piezoelectric sensors and SEN0203 sensors. The methodology involved designing a cardiac monitoring device that integrates both sensors to simultaneously capture carotid pulse and phonocardiograph (PCG) signals. Data collection was conducted on 10 respondents, where both sensors were applied alternately to the carotid artery, and the signals were analyzed using an oscilloscope. The results demonstrated that the piezoelectric sensor outperformed the SEN0203 sensor in terms of signal clarity and amplitude. Specifically, the average amplitude of the carotid pulse recorded by the piezoelectric sensor was 5.3 mV, while the SEN0203 sensor recorded an average amplitudeof only 3.2 mV. Additionally, the correlation analysis revealed a strong relationship between the carotid pulse and PCGsignals, with a correlation coefficient of 0.87, indicating a high degree of reliability in the measurements obtained fromthe piezoelectric sensor. In conclusion, the findings of this study suggest that piezoelectric sensors are more effectivefor monitoring carotid pulse signals compared to SEN0203 sensors, providing clearer and more reliable data. Thisadvancement in sensor technology has the potential to improve early detection of cardiovascular abnormalities, leadingto better patient outcomes. Future research should focus on the development of portable monitoring devices thatincorporate these sensors, facilitating widespread clinical application and enhancing the overall quality of cardiovascularcare.